2020
DOI: 10.3390/catal10080890
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Effect of Nickel Particle Size on Carbon Formation Type in the Methane Decomposition Reaction

Abstract: Carbon species deposition is recognized as the primary cause of catalyst deactivation for hydrocarbon cracking and reforming reactions. Exploring the formation mechanism and influencing factors for carbon deposits is crucial for the design of rational catalysts. In this work, a series of NixMgyAl-800 catalysts with nickel particles of varying mean sizes between 13.2 and 25.4 nm were obtained by co-precipitation method. These catalysts showed different deactivation behaviors in the catalytic decomposition of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…CMD reaction is also structurally sensitive to Ni particle size where small Ni particles show high methane decomposition activity 146 . This can be explained by the lower activation barriers of methyl species dissociation on uncoordinated crystallographic planes such as Ni (553) or Ni (100) compared with the packed surface Ni (111), which are greater on small‐sized particles 146,147 . Different from small Ni particles, a large amount of Ni (111) surfaces exists on the large Ni particles.…”
Section: Ni‐based Catalystmentioning
confidence: 99%
See 2 more Smart Citations
“…CMD reaction is also structurally sensitive to Ni particle size where small Ni particles show high methane decomposition activity 146 . This can be explained by the lower activation barriers of methyl species dissociation on uncoordinated crystallographic planes such as Ni (553) or Ni (100) compared with the packed surface Ni (111), which are greater on small‐sized particles 146,147 . Different from small Ni particles, a large amount of Ni (111) surfaces exists on the large Ni particles.…”
Section: Ni‐based Catalystmentioning
confidence: 99%
“…The difference affects the mechanism for CNTs growing on large and small Ni particles as visualized in Figure 9. Through multiple characterizations, it is revealed that larger Ni particles are more likely to induce the formation of CNTs, while smaller Ni particles promote the formation of encapsulated carbon 146 …”
Section: Ni‐based Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalytic activity and stability of 15Cu-50Ni/Al 2 O 3 were higher than monometallic Ni catalysts. NiMgAl mixed oxide catalysts were prepared using the precipitation method with various nickel nanoparticles ranging from 13.2 nm to 25.4 nm to determine the effect of nanoparticle size on the type of carbon product [ 82 ]. The carbon type depended on the Ni nanoparticle size significantly.…”
Section: Metal-based Catalystsmentioning
confidence: 99%
“…Taking into account the effect of the size of the active phase crystallites on the type of formed carbon deposit, it is suggested that smaller metal particles enhance the formation of encapsulating carbon, leading to faster deactivation of the catalyst by covering of the active phase with an impermeable carbonaceous layer. On the other hand, larger metal crystallites (above 6-7 nm) facilitate the production of filamentous carbon with Ni particles located on the top of formed filaments [22]. In the second case, filamentous carbon can be produced by the transformation of carbon oxide via the Boudouard reaction or its reduction to carbon and the decomposition of light hydrocarbons (mainly methane).…”
Section: Formation Of Coke Depositmentioning
confidence: 99%